Photosynthetic biogas upgrading using microalgae: Effect of light/dark photoperiod. (June 2017) - Meier, L.; Barros, P.; Torres, A.; Vilchez, C.; Jeison, D.
Abstract: The use of biogas for grid injection or vehicle fuel requires purification steps to obtain biomethane, process normally called biogas upgrading. The use of microalgae cultures has been proposed as a new alternative for CO2 removal from biogas. Full-scale systems for biogas upgrading using microalgae should be able to deal with natural existing day/night photoperiods. This research evaluated the effect of a light/dark photoperiod on the operation of a photosynthetic biogas upgrading system, at lab-scale conditions. A system based on an open-photobioreactor connected to a mass transfer column was used for that purpose. Using a continuous biogas flow, an upgraded biogas with a CO2 concentration between 2 and 4.5% was obtained throughout light and dark periods. O2 concentrations below 1% in final biogas were observed. Mass balances showed that CO2 desorption was the main process behind CO2 removal. CO2 removal during the dark phase was possible, under the tested conditions, as a result of inorganic carbon desorption from the photobioreactor and accumulation in the liquid phase. Highlights: Biogas can be upgraded continuously during light/dark cycle using a photobioreactor. Desorption from reactor and accumulation as HCO3 − enabled CO2 removal overnight. CO2 desorption was the main mechanism of carbon removal from photobioreactor. Temperature decrease during dark-time enhanced CO2 absorption.